Savonius vertical axis wind turbine (VAWT) - Chen, Zhengnian. (2012)
In recent years, there has been increasing awareness of the energy crisis that followed our unsustainable exploitation of fossil fuels and this has sparked interests in developing alternative methods to fuel our ever increasing energy needs. One such alternative sources of energy is the wind. Although much progress has been achieved in extracting energy from high velocity wind on wind farms etc, much improvement still awaits in the design of wind turbines that are able to extract wind energy from areas where the wind speeds are low, or have winds coming from different directions. Vertical axis wind turbines such as the Savonius turbine seems promising for such conditions. Thus, this project aims to improve on the efficiency of the Savonius turbine, taking into account investigations that have been made to date. A new design is built and tested in a wind tunnel and data collected for evaluation